Evaluation of Positive Parenting Training Program in Improving Mental Health of Children - Yunike Yunike; Ira Kusumawaty (Budapest International Research and Critics University, 2022)
Increased stressors due to Pan for Covid-19 has an impact negative on pattern nurturing so which brings up mental problems in children, including addicted gadgets, behavior rude, cyberbullying, and problems with psychology. Intervention training is needed to Upgrade positive parenting abilities. Research objectives to describe the design and rationale for randomized controlled trials evaluating the effects of training programs online-based care on parents and their impact on children's mental health in the population Sekolah Alam. Method: The study uses a design mixed method type embedded experimental model sequential explanatory. Respondent is father or Mother at least 18 years old, incorporated in community Sekolah Alam, have at least 1 child aged 8-12 years, totaling at least 180 people. Intervention given for 5 weeks online, continued accompaniment through Whatsapp Group for 6 months. Data collected covers opinions about parenting models, patterns of communication, and systems enforcement discipline, as well as evaluation of children's mental health. Results: Study this evaluate protocol training from offline to online to adapt to restrictions on the Covid-19 Pandemic. This Research will determine whether the training program nurturing could be used in positive parenting practices to prevent problems mental health of certain populations. If it's proven effective, this program potentially improved, adapted, and implemented in population special other.